Modelling and optimizing flights diversion due to destination airport closure - Zhao, Xiangling; Zhang, Yu (Transport, 2026)
With the fast development of civil aviation, large number of flights operate in major airports in rush hour. Extreme natural disasters, terrorism, and incidents may interrupt its normal operation, even lead temporary closure. Abrupt airport outage causes significant flights diverting to alternate airports. In this article, a centralized optimization method is proposed for the management and optimization of widespread flight diversion. Based on the idea of Collaborative Decision-Making (CDM), a linear programming model formulation is developed to assign flights, who are inbound to a temporary closed destination airport in an emergency, to divert to appropriate alternate airports. The objectives are minimizing total diverting time of flights as well as maximizing the expectation to alternate airports for airlines. Incorporating relevant real-world features, flights remaining flying time available and expectation of alternate airports are taken into account from airlines operation perspective. Airport alternate capacity, the category of aircraft could be accepted and the arriving flight slots assigned are considered for alternate airports. In addition, aircraft cruise speed, en-route wind, air traffic congestion and so on is considered. In the case study, it is found that under the given condition of 50 flights and 8 alternate airports, all flights can be accommodated within the remaining flying time, 33 (66%) flights are less 60 min and 48 (98%) flights are less than 120 min. The model solving time expenditure is less than one 2nd. It can meet the emergency condition and prevent a longer decision-making process. Comparing with the objective of the shortest diverting time as literature, the total diverting time is suboptimal but the formulation can get a better expectation of alternate airports for flights, which provides more flexibility of operations in airlines.